Realization of Good Governance Through Medan One Data Program as a Form of Regional Autonomous Implementation of Medan City Government - Ali Yusran Gea (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The concept of good governance can be realized if the three main actors, namely the government, private sector and civil society, synergi ze with each other. The one data program is closely related to the concept of good governance. This concept is better interpreted as a solution to realize effective and efficient government performance in the city of Medan. The Medan One Data Program has several main objectives and benefits in improving good governance in Medan City. Here are some of them: Increasing Transparency, Efficiency of Decision Making, Reducing Redundancy and Reducing Costs, Improving Public Services, Performance Monitoring and Evaluation, Community Empowerment. The initiative is a Presidential mandate as specified in Presidential Regulation No. 39 of 2019. The research method used in this research is a qualitative descriptive method that describes conditions and phenomena found in the field. Thus, the research results show that the one data program can increase the effectiveness of Medan City government implementation. The Medan One Data Program not only helps improve the efficiency and effectiveness of government administration, but also strengthens the principles of good governance, transparency, community participation and accountability in the administration of Medan City government.